Early – versus late-onset preeclampsia: differences in risk factors and birth outcomes - Markin L.; Medvyedyeva O. (Львівський клінічний вісник)
Introduction. Preeclampsia (PE) continues to be a leading cause of maternal and fetal morbidity and mortality worldwide with an incidence of 3–5 %. Recently evidence suggests that PE can be subdivided into early-onset PE (EOP), requiring delivery before 34 weeks’ gestation and late-onset PE (LOP), with delivery at or after 34 weeks. They are associated with different maternal and fetal outcomes, biochemical markers, heritability, and clinical features. Although the diagnostic criteria are the same in each of these phenotypic variants of preeclampsia, they are characterized by different clinical features and are associated with different maternal and fetal outcomes. Within the context of personalized medicine, future lines for investigations dealing with the prediction and prevention of PE should be based on the identification of the PE subtypes with regard to the maternal characteristics and clinical factors. Aim. The aim of this study was to study the incidence of early-onset and late-onset preeclampsia at a tertiary care center (at obstetrical department of L’viv Regional Clinical Hospital) and to find the difference in risk factors and birth outcomes associated with early-onset and late-onset preeclampsia. Materials and methods. Clinical and anamnestic data were analyzed for 300 pregnant women aged 16-43 years old with singleton pregnancies divided into 3 groups: group I consisted of 100 patients with early-onset preeclampsia, group II – 100 patients with late-onset preeclampsia; group III (control) consisted of 100 normotensive pregnant women who delivered consecutively after preeclamptic pregnant women. Preeclampsia was defined according to the criteria of the International Society for the Study of Hypertension in Pregnancy. EOP was defined as onset of disease from 20 weeks 0 days to 33 weeks 6 days, whereas LOP was regarded as PE after 34 weeks’ gestation. Results. Our study shows that effect of risk factors such nulliparity, chronic hypertension, and diabetes vary according to the subtype of preeclampsia. For example, women who were young (younger than 20), nulliparous, had diabetes mellitus were significantly associated with increased risk of LOP, whereas women who had chronic hypertension, congenital anomalies had higher rates of EOP. Several risk factors were associated with preeclampsia, without a significant difference for early and late-onset disease. Maternal age more than 35 years, pregestational BMI more than 25, smoking during pregnancy were significantly associated with increased risk of both EOP and LOP. The rates of all adverse birth outcomes, were higher among women with EOP. For example, the rates of fetal, neonatal and perinatal death were significantly higher in the EOP group than in LOP group. The rates of NICU admission and severe neonatal morbidity were significantly higher among infants born to mothers with EOP. Conclusions. Our research revealed that EOP is a distinct and a more severe clinical entity, associated with intrauterine growth restriction, with high rates of adverse birth outcomes, with a much earlier gestational age at onset and delivery. EOP starts with a failure to transform the maternal spiral arteries, subsequently followed by alterations of the villous trophoblast, lead to severe placental lesion (early placental dysfunction), hypoxia of the placenta and fetus, the failure of compensatory mechanisms, an increase endothelial dysfunction markers. Therefore, this subtype of preeclampsia debuted early (in the midtrimester) and leads to worse perinatal outcomes. In comparison, LOP develops in the third trimester of pregnancy, rarely leads to perinatal loss.